1998
DOI: 10.1021/jp972788m
|View full text |Cite
|
Sign up to set email alerts
|

Modification of MCM-41 by Surface Silylation with Trimethylchlorosilane and Adsorption Study

Abstract: Siliceous MCM-41 samples were modified by silylation using trimethylchlorosilane (TMCS). The surface coverage of functional groups was studied systematically in this work. The role of surface silanol groups during modification was evaluated using techniques of FTIR and 29Si CP/MAS NMR. Adsorption of water and benzene on samples of various hydrophobicities was measured and compared. It was found that the maximum degree of surface attachments of trimethylsilyl (TMS) groups was about 85%, corresponding to the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
366
3
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 493 publications
(397 citation statements)
references
References 25 publications
25
366
3
3
Order By: Relevance
“…Its pore diameter is ranged between 20-30 Å and its surface area is about 700-900 m 2 g -1 (Chiarakorn et al 2007). This material has been introduced to be an alternative adsorbent for the adsorption of various air pollutants, supporting material for catalytic reaction, ion exchange media and filter (Appaturiet al 2012;Artklaet al 2009;Beck et al 1992;Chumeeet al 2009;Klankawet al 2012;Tong-On et al 2009;Wantalaet al 2010;Yoshitakeet al 2002;Zhao & Lu 1998). Nevertheless, it was reported that the hydrophilicity of surface caused low adsorbability when MCM-41 is applied for non-polar volatile organic compounds (VOCs) adsorption under high relative humidity condition (Branton et al 1999;Idris et al 2010;Ohashi et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its pore diameter is ranged between 20-30 Å and its surface area is about 700-900 m 2 g -1 (Chiarakorn et al 2007). This material has been introduced to be an alternative adsorbent for the adsorption of various air pollutants, supporting material for catalytic reaction, ion exchange media and filter (Appaturiet al 2012;Artklaet al 2009;Beck et al 1992;Chumeeet al 2009;Klankawet al 2012;Tong-On et al 2009;Wantalaet al 2010;Yoshitakeet al 2002;Zhao & Lu 1998). Nevertheless, it was reported that the hydrophilicity of surface caused low adsorbability when MCM-41 is applied for non-polar volatile organic compounds (VOCs) adsorption under high relative humidity condition (Branton et al 1999;Idris et al 2010;Ohashi et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…To resolve this drawback, the surface modification via silylation has been introduced. Generally, the silylation is a well-known technique for surface tailoring on several materials containing silanol groups such as MCM-41, MCM-48, SBA-1 and silica gels (Deschner et al 2010;Koyano et al 1997;Lin et al 2008;Yokoi et al 2004;Yuan et al 2006;Zhao & Lu 1998). The common reagents used for the silylation are organosilanes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao and Lu* (1998) was studied the modification of MCM41 by surface silylation with trimethylchlorosilane and adsorption study. They found the surface chemistry of MCM41 can be effectively modified to be more hydrophobic by chemical attachment of organic species and be an effective technique in selective adsorbents for the removal of organic compounds from streams or wastewater [5].…”
Section: Introductionmentioning
confidence: 99%
“…The MCM-41 surface structure is covered with silanol groups (Si-OH) formed during the synthesis of the material [9,10]. The hydrophilic characteristic of the material is attributed to the existence of these Si-OH groups.…”
Section: Introductionmentioning
confidence: 99%